A Two-Dimensional Numerical Study of Evaporation by Mixed Convection of an Inclined Damp Flat Plate: A Lean Engineering Approach Using DMADV Methodology - Dimbiharizafy, Ando; Rakotozandry, Andriamananarivo Ignace; Randriamorasata, Josoa (International Journal of Environment, Engineering and Education, 2025)
This paper presents a two-dimensional numerical study of the evaporation by mixed convection of an inclined damp flat plate subjected to a constant heat flux density. Airflow, heat, and mass transfers are governed by the equations of continuity, motion, energy, and diffusion, to which boundary layer approximations are applied. Adimensionalization, implicit finite difference method, and programming on MATLAB are used to solve the equations. The methodology is designed using the FAST (Function Analysis System Technique) method and reinforced with DWADV (Define, Measure, Analyze, Design, Verify) by applying Lean Engineering and Six Sigma. The approximation in the boundary layer makes it possible to reduce the number of terms in the equations of the problem. Adimensionalization links the parameters together and reduces their number. The quantities studied no longer depend on the measurement system. Comparison with other studies allowed us to validate our results. The work ends with presenting results about the influence of the Richardson number and the flat’s inclination on non-dimensional velocity, non-dimensional temperature, non-dimensional concentration, and coefficients of exchange associated with mixed convection: friction coefficient, Nusselt and Sherwood number. The increase in the value of the Richardson number generates the opposite effect of the increase in the inclination of the plate on the parameters of mixed convection and the exchange coefficients.